Keanekaragaman Lumut Kerak (Lichenes) di Area Kaki Gunung Mutis - Kamaluddin; Emanuel M. Y. Hano’e; Lukas Pardosi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The aim of the study was to explore, identify and describe the types of Lichenes in the foothills of Mount Mutis in Eban Village. This research was conducted in April-July 2022 using a qualitative descriptive approach with the reconassance method. Sampling used a purposive sampling technique by taking samples, collecting and collecting them to assist in the laboratory. The results of research that have been carried out by lichens found at the foot of Mount Mutis, Eban Village, West Miomaffo District, amount to 21 types of lichen species with descriptions: Leptogium azureum, Pertusaria sp, Lepraria Loficans, Lepraria incana, Parmelia saxatilis, Parmotrema tinctorum, Cetrelia olivetorum, Heterodermia japonica, Usnea hirta, Parmotrema perlatum, Graphis scripta, Graphis sp 1, Graphis sp 2, Haematomma accolens, Cryptothecia striata, Bacidia schweinitzii, Bacidia sp, Dirinaria applanate, Opegrapha gyrocarpa, Lecidella elaeochroma, Caloplaca ferruginea. The most common lichen groups were the 12 families Parmeliaceae most commonly found in research lines with 5 species, Graphidaceae 4 species, Bacidia 2 species, Stereocaulaceae 2 species, and Collemataceaee, Pertusariaceae, Haematommataceae, Artho-niaceae, Physciaceae, Opegraphaceae, Lecidellaleceae, Teloschistaceae 1 species each. Lichen substrate found living on tree trunks, tree stalks and rocks. The form of lichen thallus that was most commonly found was Crustose which was 62%, then Foliose thallus was 33% and Fruticose was 5%. The diversity of mosses in the study area is strongly influenced by both abiotic and biotic environmental factors. The type of Licen found in Eban Village is a Lichen which is able to adapt to an environment which incidentally is dominated by dry land.